Coccolithophore content of plankton samples in the southwestern Gulf of Mexico - Karl-Heinz Baumann; Babette Boeckel (PANGAEA, 2025)
Plankton samples from 6 stations taken during the Meteor cruise M67/2 in March 2006 were analyzed for their coccolithophore content. Using a scanning electron microscope, a total of 39 species were observed, with only eight species making a significant contribution to the species community, and a clear vertical stratification in the coccolithophores was observed.